CONTEMPORARY TENDENCIES IN SPORT WRESTLING - Goran Kasum; Mališa Radović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Most authors separate all wrestling styles and disciplines into Folk style and Sport wrestling. Sport or International wrestling are those styles of wrestling which are spread all around the world, are internationally recognised, and have unique organization and rules in the whole world. The group of wrestling folk styles includes all wrestling styles existing today, all wrestling styles which existed in the past, on certain territories or certain ethnic communities, but have no global character. The number of such styles is extremely high, and in technical literature, there are more than 200 described wrestling styles. Sport wrestling includes three Olimpic wrestling styles ( Greco - Roman, Freestyle wrestling and wrestling for women), including the non - Olympic wrestling style, Sambo. Apart from these wrestling styles many authors consider judo as a wrestling sport style, which can be apsolutely logically based and justified. However, due to both general climate and requirements of the audience, the wrestling sport style now incorporates certain wrestling styles which have been developed as a contemporary modification of some ancient and well-known wrestling styles. Not until two years ago, the International Federation of Associated Wrestling Styles, FILA, has accepted Beach wrestling, Grappling and Pankration as internationally developed and recognized styles of sport wrestling. By analizing specificities of these wrestling sport styles and recognizing modification of the established rules of the well-known Olympic wrestling styles, it is possible to distinguish certain tendencies and regularities. The recognised regularities announce, in a way, some trends and tendencies to be developed in the future. Recognition and understanding of these tendencies in due time, will contribute to faster progress of wrestling along with increasingly high popularization of this sport.